Perceptions of the SRI Nakharinwirot University teachers and fourth year college students on social studies instruction at Mahasarakham, Thailand - Vichian Amphonrugsha 1937- (1978)
This study sought to find out the perceptions of Fourth Year College students in Sri Nakharinwirot University at Maharasakham, Thailand on Social Studies Instruction in relation with other academic subjects. It aimed to clarify the views of the students on the method of teaching in their Social Studies subject as well as their views on the content of the course.